Evaluation of Judet view radiographs accuracy in classification of acetabular fractures compared with three-dimensional computerized tomographic scan: a retrospective study - Tazeabadi, Sepideh Abdi (BMC Musculoskelet Disord, 2020)
BACKGROUND: In the current diagnostic procedure, generally, both plain radiographs and 3D-CT scans are used for the diagnosis of acetabular fractures. There is no consensus regarding the value of a three-dimensional computerized tomographic (3D-CT) scan alone in the classification of acetabular fractures. In this study, we compared the accuracy of 3D-CT scan and plain radiography through the evaluation of their agreement with the intraoperative surgeon’s classification. METHOD: In a retrospective study, patients who were referred to our center with an acetabular fracture and underwent surgical treatment were included. The classification of acetabular fractures was performed once using Judet view plain radiographs and once using a 3D-CT scan by the corresponding one Experienced musculoskeletal radiologist one independent trauma fellowship-trained orthopaedic who routinely treat acetabular fractures and based on Letournel and Judet classification (17 and 23 years of experience respectively). Cohen’s kappa value was used for the assessment agreement between the two imaging modalities, as well as between the imaging modalities and intraoperative classification. RESULTS: Medical files of 152 patients with acetabular fracture were retrospectively reviewed. A kappa value of 0.236 was obtained as the agreement level between radiographs and intraoperative findings (p < 0.001). A kappa value of 0.943 was obtained as the agreement level between 3D-CT and intraoperative classification (p < 0.001). An agreement level of 0.264 was found between the Judet radiographs and 3D-CT scans (p < 0.001). CONCLUSIONS: 3D-CT scans are reliable enough in the classification of acetabular fractures, and plain radiographs could be omitted to avoid radiation exposure as well as to reduce the cost for patients who sustain acetabular fractures.